Determinants of urban land supply in the people's republic of China : how do political factors matter? - Hsu, Wen-Tai (2018)
This paper explores whether and how corruption and competition-for-promotion motives affect urban land supply in the People's Republic of China. Conditional on demand-side factors, we find that corruption is highly correlated with an increase in land supply. The corruption effects are strongest for commercial land, followed by residential land, and then industrial land. To shed light on the competition motives among prefectural leaders, we examine how the number of years in office affects land supply and distinguish among different hypotheses. Our empirical results show robust rising trends in land sales. These results are consistent with the hypothesis that among prefectural leaders the impatience and anxiety in later years from not being promoted may contribute to an increase in land sales revenue in later years. We also find that prefectural leaders may aim for more land sales revenue over their first few years in office instead of seeking higher revenue in their first 1–2 years.